Контроль якості хромонікелевих сталей за парамагнітним станом аустеніту - Сніжной, Геннадій Валентинович; Сніжной, Валентин Лук'янович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
The subject matter of the article is the processes of monitoring and assessing the quality of austenitic chromium-nickel steels. The quality of steels and products made from them depends on the combination of physical, chemical and technological properties that are formed as a result of the phase-chemical composition and various types of processing (temperature, deformation, laser, radiation, etc.). Determination of a methodology that will supplement or replace multiple tests by measuring one parameter is highly relevant.  The goal is to find a methodology for a comprehensive assessment of mechanical and corrosion properties in one parameter, which is sensitive to external factors. It is proposed to use the specific paramagnetic susceptibility of austenite c0 as an integral characteristic of the influence of various factors (chemical composition, melting conditions, deformation, temperature, etc.). Parameter c0 is a characteristic of the atomic-magnetic state of austenite and a sensitive quantity to the influence of external factors. The tasks to be solved are: to formalize the correlation between the specific paramagnetic susceptibility c0 of austenite and mechanical, corrosion properties (tensile strength sв, conditional yield stress s0.2, elongation d, corrosion rate K). The methods used are: a highly sensitive magnetometric method for determining the specific magnetic susceptibility X and the low content of the ferromagnetic phase of the samples of the studied steels in the initial state (before mechanical and corrosion tests). Mechanical indicators were determined in accordance with GOST 1497-84, the value of corrosion losses in chloride-containing solutions - in accordance with GOST 9.912-89.  The following results were obtained. It has been experimentally established that the tendency of changes in the mechanical and corrosion properties of steels of the AISI 321 and AISI 304 types correlates with the magnetic nature of the paramagnetic austenite matrix, which is determined by the sum of the magnetic moments of atoms per unit mass (specific magnetization). Conclusions. It is shown that the specific paramagnetic susceptibility of austenite can be used to determine the behavior (increase or decrease in mechanical and corrosion properties). It is shown that a low content of d-ferrite can also be a measure (indicator) of the behavior of these properties.